Pengaruh Keteladanan Guru PAUD Terhadap Karakter Anak Usia 5-6 Di PAUD SOS Sitabotabo - Citra Natalia Aruan; Julita H. Pakpahan; Emmi Silvia Herlina (Journal of Creative Student Research, 2023)
The purpose of this study was to determine the effect of the PAUD teacher's example on the character of children aged 5-6 year at PAUD SOS HKBP Sitabotabo. The method used in this research is descriptive quantitative. The population is all children aged 5-6 years in PAUD SOS HKBP Sitabotabo, totaling 32 people. Data were collected using a positive closed questionnaire of 30 items of which 11 questionnaire items were for variable X and 19 questionnaire items were for variable Y. The results of data analysis showed that there was an exemplary effect of PAUD teachers on the character of children aged 5-6 years in PAUD SOS HKBP Sitabotabo. Analysis requirements test, a positive relationship test obtained a value of rxy = 0.724 > rtable(α =0.05, n=32) = 0.349 thus it is known that there is a positive relationship between variable X and variable Y, Relationship test a significant value obtained tcount = 5.753 > ttable (α = 0.05,dk =n-2=30) = 2.042 thus there is a significant relationship between variable X and variable Y. Effect test, Test the regression equation, the regression equation = 9,57 +1.42X is obtained, Test the coefficient of determination regression (r2) = 52.5%. Thus Ha is accepted and H0 is rejected.